Preemptive oral analgesia with steroidal and nonsteroidal anti-inflammatory drugs in periodontal surgery: a systematic review - Lages, Lívio Portela de Deus; Bergamaschi, Cristiane de Cássia; Lopes, Luciane Cruz; da Frota, Eduardo Gomes; Silva, Marcus Tolentino; Monte, Thiago Lima; Motta, Rogério Heládio Lopes (Frontiers in Pharmacology, 2024)
Periodontal procedures can promote prolonged intense pain, particularly in clinical situations requiring surgical procedures. In this context, preemptive analgesia has also been assessed for its utility in controlling post-operative pain and discomfort in patients undergoing periodontal invasive procedures. This study assessed the efficacy and safety of preemptive oral analgesia with steroidal and non-steroidal anti-inflammatory drugs in periodontal surgeries. This systematic review performed a search in the following electronic sources: the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE (via PubMed), EMBASE (via Ovid), Web of Science, Virtual Health Library and in clinical trials electronic databases for relevant randomized clinical trials (RCTs); published up to July 2023. Primary outcomes assessed were post-operative pain, edema and trismus. A narrative synthesis of the findings was carried out. Six RCTs, involving a total of 250 participants, were included. The studies reviewed had a high risk of bias, particularly due to allocation concealment and blinding of participants and personnel. The RCTs reported only the outcome pain. The preemptive use of dexamethasone 8mg, etoricoxib 90mg or 120mg and ketorolac 20mg seems to be more effective for controlling post-operative pain than placebo. The anti-inflammatory drugs evaluated proved to be effective for controlling post-operative pain. However, given the limitations regarding lack of studies, methodological biases, disparities in drugs and doses, report restricted the pain outcome; further RCTs confirming the effectiveness and safety of these drugs in periodontal surgical procedures are warranted.